KEMAMPUAN PENALARAN MATEMATIKA DAN SELF-EFFICACY SISWA SMP - Aprisal Aprisal; Sartika Arifin (Universitas Pekalongan, 2020)
This study is a survey research using quantitative approach. The subject in this study was eighth grade students with 132 students. Data in this study were collected using two instruments, namely mathematics reasoning ability tests and self-efficacy questionnaires. Analysis of the data in this study was divided into two parts, namely descriptive analysis and inferential analysis. Descriptive analysis described of mathematical reasoning ability and self-efficacy. Inferential analysis used Pearson product moment correlation test to find relationship between self-efficacy and mathematical reasoning ability. The results of the study showed that the students' self-efficacy was in high category and the strength aspect was the dimension of self-efficacy with the highest score. In mathematical reasoning ability, the ability of students to give correct and complete evidence of solutions has the highest score. The result of correlation test showed that there was relationship between self-efficacy and mathematical reasoning ability with a positive relationship